2021
DOI: 10.1093/psyrad/kkaa003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of jet lag on brain white matter functional connectivity

Abstract: Background A long-haul flight across more than five time zones may produce a circadian rhythm sleep disorder known as jet lag. Little is known about the effect of jet lag on white matter (WM) functional connectivity (FC). Objective The present study is to investigate changes in WM FC in subjects due to recovery from jet lag after flying across six time zones. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…According to the spatial location, we named them WM1 (superior longitudinal fasciculus network), WM2 (inferior longitudinal fasciculus network), WM3 (anterior corpus callosum network), WM4 (corpus callosum network), WM5 (occipital network), WM6 (inferior temporal), WM7 (prefrontal network), WM8 (superior corona radiata network), WM9 (post-central network), WM10 (cerebellar network), WM11 (posterior callosum network), WM12 (inferior frontoparietal network), and WM13 (deep network). The present networks WM3, WM4, WM5, WM7, WM8, WM9, and WM13 are similar to the results of the previous researches ( Jiang et al, 2019a ; Li et al, 2022 ), while the other WM networks can also be obtained in some studies ( Peer et al, 2017 ; Zhang et al, 2021b ). Consistent with previous studies, these WM networks can be divided into three layers (superficial, middle, and deep) ( Jiang et al, 2019a ; Fan et al, 2020 ) (shown in Figure 3A ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…According to the spatial location, we named them WM1 (superior longitudinal fasciculus network), WM2 (inferior longitudinal fasciculus network), WM3 (anterior corpus callosum network), WM4 (corpus callosum network), WM5 (occipital network), WM6 (inferior temporal), WM7 (prefrontal network), WM8 (superior corona radiata network), WM9 (post-central network), WM10 (cerebellar network), WM11 (posterior callosum network), WM12 (inferior frontoparietal network), and WM13 (deep network). The present networks WM3, WM4, WM5, WM7, WM8, WM9, and WM13 are similar to the results of the previous researches ( Jiang et al, 2019a ; Li et al, 2022 ), while the other WM networks can also be obtained in some studies ( Peer et al, 2017 ; Zhang et al, 2021b ). Consistent with previous studies, these WM networks can be divided into three layers (superficial, middle, and deep) ( Jiang et al, 2019a ; Fan et al, 2020 ) (shown in Figure 3A ).…”
Section: Resultssupporting
confidence: 90%
“…For instance, Jiang et al found that patients with schizophrenia showed increased FC in the perception-motor white-matter network ( Jiang et al, 2019a ). More recently, the abnormalities of FC in the white-matter functional network were also revealed in other diseases, including epilepsy, attention deficit hyperactivity disorder, bipolar disorder, schizophrenia, Parkinson’s, and depression ( Jiang et al, 2019a , b ; Bu et al, 2020 ; Fan et al, 2020 ; Li et al, 2020 ; Lu et al, 2021 ) and even in participants with orthodontic pain or jet lag ( Zhang et al, 2021a , b ). Taken together, these studies provided strong evidence of the existence of functional brain activity in the white-matter and suggested that the functional information from white-matter can be detected by fMRI.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Functional changes in the cingulum were associated with recovery from jetlag, which can be interpreted as re-alignment after circadian disruption. 9 However, it remains unclear why the increased FA correlated with poor sleep quality in shift workers but not in non-shift workers. A future study featuring long-term longitudinal imaging is required.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep quality has been associated with structural white matter changes. [8][9][10][11] Previous studies reported that white matter alterations were related to the sleep quality of college students 10 and older adults. 11 A relationship between white matter integrity and sleep quality has also been observed in patients with insomnia.…”
Section: Introductionmentioning
confidence: 99%